Antibacterial efficacy from NO-releasing MOF–polymer films. Issue 7 (7th October 2020) - Duncan, Morven J.; Wheatley, Paul S.; Coghill, Emma M.; Vornholt, Simon M.; Warrender, Stewart J.; Megson, Ian L.; Morris, Russell E.
Abstract : Sufficient concentration of nitric oxide is released from metal organic framework loaded polymer films to impart antibacterial efficacy. Abstract : The formulation and antibacterial efficacy of nitric oxide (NO)-releasing MOF–polyurethane films are reported for the first time. Uniform standalone films were successfully prepared containing 1, 5, 10, and 15 wt% CPO-27 (Ni). The MOF within each film was successfully activated and loaded with NO. Adsorption and release profiles are reported for the films and show that while the polymer influences the quantity of NO adsorbed and stored by the MOF and the time scale of release; the proportion of stored NO that is released is dependent on wt% loading of MOF in the film. In a cytotoxicity assay, the formulations exhibited very low toxicity (<20% cell death), and this toxicity was attributed to the NO rather than the MOF. Antibacterial data against E. coli and S. aureus indicated that bactericidal efficacy can be achieved in 5 hours from 1 wt% films, and within 1 hour for films containing at least 5 wt% MOF.